Experimental Study on the Utilisation of Independent Wire Fibre Core Steel Wire Rope Braces to Enhance the Stability of a 2d Concrete Portal against Lateral Forces - Zarkasi, Ahmad; Fitrayudha, Adryan; Hidayati, Nurul; Santika, Yuliana; Marsa D.P, Khendy (Newinera Publisher, 2025)
Structural stability in construction, especially in buildings exposed to lateral forces due to earthquakes, is very important to consider. This research aims to explore the effectiveness of using Independent Wire Fibre Core (IWFC) steel wire rope braces in strengthening two-dimensional (2D) concrete portals. The method used is a series of laboratory tests to measure the performance of concrete portals equipped with IWFC braces. Concrete portals with dimensions of 1.00 m in the width direction and 1.50 m in the height direction were tested with lateral loading to simulate the effects of earthquakes. The test results showed that the use of IWFC braces increased the load resistance capacity of the portal by 16.13%, from 14.00 kN to 26.13 kN, and reduced the deviation by 30.43%, from 2.30 mm to 1.68 mm. In addition, the analysis showed an increase in the response modification factor (R) from 4.69 to 5.03, while the Cd value of the non-braced portal was 3.29 using braces was 3.02 and the Ω0 value of the non-braced portal was 3.50 and after using braces was 2.84. These findings open up opportunities for the application of better structural strengthening techniques in order to improve the safety and stability of buildings in earthquake-prone areas.